2014
DOI: 10.1117/12.2045277
|View full text |Cite
|
Sign up to set email alerts
|

Design, characterization, and testing of macro-fiber composite actuators for integration on a fixed-wing UAV

Abstract: Smart materials offer several potential advantages for UAV flight control applications compared to traditional servo actuators. One important benefit is that smart materials are lightweight and can be embedded directly into the structure of a wing or control surface. Therefore, they can reduce the overall weight of the vehicle and eliminate the need for mechanical appendages that may compromise the form factor of the wing, benefits that become more significant as the size of the vehicle decreases. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Modelling piezoelectric actuators in the unimorph and bimorph set ups has been typically performed under the assumption that it acts as a beam in bending. Figure 2.3 shows a unimorph rigidly supported with the following equations formulated to predict the tip deflection [13]: Kim, Moncayo, Azizi, &Chan, 2014).…”
Section: Piezoelectric Actuatorsmentioning
confidence: 99%
“…Modelling piezoelectric actuators in the unimorph and bimorph set ups has been typically performed under the assumption that it acts as a beam in bending. Figure 2.3 shows a unimorph rigidly supported with the following equations formulated to predict the tip deflection [13]: Kim, Moncayo, Azizi, &Chan, 2014).…”
Section: Piezoelectric Actuatorsmentioning
confidence: 99%
“…As an important initial design decision, it was determined that, rather than attempting to integrate the MFC actuators into the standard foam ailerons on the Skywalker UAV, a simpler implementation would be achieved by fabricating custom ailerons for the UAS 13 . Unimorph and bimorph actuator designs were both considered for the MFC aileron design.…”
Section: Macro-fiber Composite Actuator Designmentioning
confidence: 99%
“…In several studies, the camber of the wings of a micro air vehicle (MAV) was altered using piezoelectric composites to change the lift, the drag, and the pitching moment (Bilgen and Friswell, 2014; Heryawan et al, 2005, 2006; Molinari et al, 2015; Paradies and Ciresa, 2009; Prazenica et al, 2014) or to control the roll and pitch by morphing the trailing edge near the wingtips (Bilgen et al, 2007; Probst et al, 2012; Vos et al, 2007); the feasibility of these designs has been demonstrated in flight tests (see Figure 5). An MAV in which the elevators were controlled by piezoelectric composites was constructed and tested in a wind tunnel (Yoon et al, 2006a, 2006b).…”
Section: Actuatorsmentioning
confidence: 99%